Plant species influences the composition of root system microbiome and its antibiotic resistance profile in a constructed wetland receiving primary treated wastewater - Riva, Valentina; Vergani, Lorenzo; Rashed, Ahmed Ali; El Saadi, Aiman; Sabatino, Raffaella; Di Cesare, Andrea; Crotti, Elena; Mapelli, Francesca; Borin, Sara (Frontiers in Microbiology, 2024)
Constructed wetlands (CWs) are nature-based solutions for wastewater treatment where the root system microbiome plays a key role in terms of nutrient and pollutant removal. Nonetheless, little is known on plant-microbe interactions and bacterial population selection in CWs, which are mostly characterized in terms of engineering aspects. Here, cultivation-independent and cultivation-based analyses were applied to study the bacterial communities associated to the root systems of Phragmites australis and Typha domingensis co-occurring in the same cell of a CW receiving primary treated wastewaters. Two endophytic bacteria collections (n=156) were established aiming to find novel strains for microbial-assisted phytodepuration, however basing on their taxonomy the possible use of these strains was limited by their low degrading potential and/or for risks related to the One-Health concept. A sharp differentiation arose between the P. australis and T. domingensis collections, mainly represented by lactic acid bacteria (98%) and Enterobacteriaceae (69%), respectively. Hence, 16S rRNA amplicon sequencing was used to disentangle the microbiome composition in the root system fractions collected at increasing distance from the root surface. Both the fraction type and the plant species were recognized as drivers of the bacterial community structure. Moreover, differential abundance analysis revealed that, in all fractions, several bacteria families were significantly and differentially enriched in P. australis or in T. domingensis. CWs have been also reported as interesting options for the removal of emerging contaminants (e.g, antibiotic resistance genes, ARGs). In this study, ARGs were mostly present in the rhizosphere of both plant species, compared to the other analyzed fractions. Notably, qPCR data showed that ARGs (i.e., ermB, blaTEM, tetA) and intl1 gene (integrase gene of the class 1 integrons) were significantly higher in Phragmites than Typha rhizospheres, suggesting that macrophyte species growing in CWs can display a different ability to remove ARGs from wastewater. Overall, the results suggest the importance to consider the plant-microbiome interactions, besides engineering aspects, to select the most suitable species when designing phytodepuration systems.